Ruang Damai dalam Tradisi: Mediasi Adat sebagai Jalan Tengah dalam Sengketa Warisan Perempuan Batak - Sihombing, Oktavia Permatasari; Mediana Tobing, Melati (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2025)
Inheritance disputes within the Batak community often revolve around the exclusion of daughters from receiving familial wealth due to rigid interpretations of traditional customs. However, recent shifts in societal perception have highlighted a growing awareness of gender justice and the evolving role of women in Batak families. This study explores how adat-based mediation is emerging as a peaceful and culturally rooted alternative for resolving inheritance conflicts, particularly concerning female descendants. Based on in-depth interviews, this paper uncovers narratives of change, resistance, and reconciliation. It emphasizes the value of inclusive family dialogue and the potential of adat as a flexible system that can uphold tradition while embracing fairness. The findings demonstrate that mediation rooted in local wisdom can become a middle path between cultural preservation and contemporary demands for gender equity. Keywords: Batak culture, inheritance, gender justice, adat mediation, social transformation